Pseudomonas aeruginosa in chronic lung disease: untangling the dysregulated host immune response - Nickerson, Rhea; Thornton, Christina S.; Johnston, Brent; Lee, Amy H. Y.; Cheng, Zhenyu (Frontiers in Immunology, 2024)
Pseudomonas aeruginosa is a highly adaptable opportunistic pathogen capable of exploiting barrier and immune defects to cause chronic lung infections in conditions such as cystic fibrosis. In these contexts, host immune responses are ineffective at clearing persistent bacterial infection, instead driving a cycle of inflammatory lung damage. This review outlines key components of the host immune response to chronic P. aeruginosa infection within the lung, beginning with initial pathogen recognition, followed by a robust yet maladaptive innate immune response, and an ineffective adaptive immune response that furthers propagates lung damage while permitting bacterial persistence. Untangling the interplay between host immunity and chronic P. aeruginosa infection will allow for the development and refinement of strategies to modulate immune-associated lung damage and potentiate the immune system to combat chronic infection more effectively.